Coal-derived carbon-based nickel biatomic catalyst, preparation method and application thereof
By preparing a coal-derived carbon-based nickel diatomic catalyst, the problem of structural instability of nickel single-atom catalysts was solved, and a highly efficient electrochemical catalytic effect for the reduction of carbon dioxide to carbon monoxide was achieved.
Patent Information
- Application Number
- CN202511112766.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-09
- Publication Date
- 2025-11-04
- Estimated Expiration
- 2045-08-09
AI Technical Summary
Existing nickel single-atom catalysts exhibit structural instability of the Ni-N3 active site in electrochemical carbon dioxide reduction, leading to deactivation of the active site and affecting catalytic efficiency.
A coal-derived carbon-based nickel diatomic catalyst was prepared by means of anthracite, potassium hydroxide activation, oxidant treatment, impregnation with soluble nickel salt solution and mixed carbonization with nitrogen-containing compounds to form Ni2-N6 active sites, construct an N3Ni-NiN3 diatomic structure, and stabilize the unsaturated Ni-N3 coordination environment.
It achieves high structural stability and high activity of the catalyst, improves the carbon monoxide generation rate, and achieves a Faraday efficiency of up to 98.6%, maintaining high catalytic performance over a wide potential window.
Smart Images

Figure CN120586911B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of carbon material preparation, and provides a coal-derived carbon-based nickel diatomic catalyst, a preparation method and application thereof. BACKGROUND
[0002] With the rapid development of industrialization, the large consumption of fossil energy leads to a sharp rise in the concentration of carbon dioxide in the atmosphere, causing a series of environmental and energy problems. Electrochemical carbon dioxide reduction reaction, because of its mild reaction conditions, controllable process and green process, and can convert carbon dioxide into high value-added chemicals, has shown great application prospects. However, this process often involves slow kinetics and low efficiency, and it is crucial to develop catalysts that can efficiently activate carbon dioxide at low overpotential and selectively generate target products.
[0003] Single-atom catalysts have attracted extensive attention in the field of electrochemical carbon dioxide reduction due to their extremely high atom utilization and excellent catalytic activity. Among them, nickel (Ni)-based single-atom catalysts exhibit high activity in catalyzing carbon dioxide reduction to carbon monoxide. To overcome the activity limitation of traditional Ni-N4 structure in electrochemical carbon dioxide reduction, researchers have developed highly active Ni-N3 single-atom sites with unsaturated coordination environment. However, this type of highly active Ni-N3 site has a significant bottleneck: its inherent low structural stability. Under electrochemical working conditions, especially at high overpotential or long time operation, Ni-N3 sites are prone to structural relaxation, coordination reconstruction and even metal atom aggregation, leading to deactivation of active sites, which greatly hinders its practical application. SUMMARY
[0004] The present application provides a coal-derived carbon-based nickel diatomic catalyst, a preparation method and application thereof, to solve the defect of unstable Ni-N3 active site structure in nickel single-atom catalysts in related technologies.
[0005] The present application provides a preparation method of a coal-derived carbon-based nickel diatomic catalyst, comprising the following steps:
[0006] S100, mix anthracite and potassium hydroxide by grinding to obtain a first mixture; put the first mixture into a tubular furnace for activation to obtain an activated product; sequentially wash and dry the activated product to obtain a first material;
[0007] S200, mix the first material with an oxidizing agent to obtain a second mixture; heat and oxidize the second mixture to obtain an oxidized product; dry the oxidized product to obtain a second material;
[0008] S300, immerse and stir the second material in a soluble nickel salt solution, filter to obtain a third material;
[0009] S400. Grind and mix the third material with a nitrogen-containing compound to obtain a third mixture; add the third mixture to a tube furnace for carbonization to obtain a carbide; sequentially acid-wash, water-wash, and dry the carbide to obtain a coal-derived carbon-based nickel diatomic catalyst.
[0010] According to one embodiment of the present invention, in step S100, the weight of the anthracite is 1g to 6g, the weight of the potassium hydroxide is 3g to 60g, and the feeding ratio of the anthracite to the potassium hydroxide is 1:3 to 1:10.
[0011] According to one embodiment of the present invention, in step S100, the activation temperature is 800℃~1000℃, and after reaching the activation temperature, the temperature is maintained for 1 hour~3 hours.
[0012] According to an embodiment of the present invention, the washing of the activator in step S100 includes the following steps:
[0013] S110, using a concentration of 4 mol / L -1 ~ 8mol L -1 The activated material was first acid-washed with hydrochloric acid to obtain a first wash product;
[0014] S120, using a concentration of 5 mol / L -1 ~ 10mol L -1 The first detergent is subjected to a second acid wash with hydrofluoric acid to obtain a second detergent.
[0015] S130. The second washing material is washed with water to obtain the first material to be dried.
[0016] According to one embodiment of the present invention, in step S200, the concentration of the oxidant is 4 mol / L. -1 ~ 8mol / L -1 The temperature for heating and oxidation is 80℃~100℃.
[0017] According to one embodiment of the present invention, in step S300, the concentration of the soluble nickel salt solution is 3~10 mmol / L. -1 The stirring time is 8 to 12 hours;
[0018] The soluble nickel salt solution is one of nickel chloride solution, nickel nitrate solution, or nickel sulfate solution.
[0019] According to one embodiment of the present invention, in step S400, the carbonization temperature is 900℃~1100℃, and after reaching the carbonization temperature, the temperature is maintained for 1 hour~3 hours.
[0020] According to one embodiment of the present invention, in step S400, the carbide is acid-washed, which includes the following steps:
[0021] Using a concentration of 1 mol L -1 ~ 2mol L -1 The carbides were pickled with hydrochloric acid solution for 4 to 6 hours.
[0022] The present invention also provides a coal-derived carbon-based nickel diatomic catalyst prepared by the method described above, wherein the active sites of the catalyst are Ni2-N6 and the nickel atom loading of the catalyst is 0.1%~10%.
[0023] The present invention also provides the application of the coal-derived carbon-based nickel diatomic catalyst prepared by the method described above or the method described above in the preparation of the coal-derived carbon-based nickel diatomic catalyst in the electroreduction reaction of carbon dioxide.
[0024] This invention provides a coal-derived carbon-based nickel diatomic catalyst, its preparation method, and its application. By using anthracite as the carbon source, nitrogen-containing compounds as the nitrogen source, and a soluble nickel salt solution as the nickel source, the coal-derived carbon-based nickel diatomic catalyst is prepared through activation, oxidation, and high-temperature carbonization. This achieves high-value utilization of anthracite, with low cost, simple process, and high yield. The prepared coal-derived carbon-based nickel diatomic catalyst exhibits good catalytic performance. The active sites of this catalyst are Ni2-N6, and its structure is stable. Simultaneously, it can effectively reduce the formation energy barrier of carboxyl intermediates and accelerate the formation rate of carbon monoxide. Attached Figure Description
[0025] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0026] Figure 1 This is a scanning electron microscope image of the coal-derived carbon-based nickel diatomic catalyst prepared in Example 1 of the preparation method of the coal-derived carbon-based nickel diatomic catalyst provided by the present invention.
[0027] Figure 2 This is a transmission electron microscope image of the coal-derived carbon-based nickel diatom catalyst prepared in Example 1 of the preparation method of the coal-derived carbon-based nickel diatom catalyst provided by the present invention.
[0028] Figure 3is the electron diffraction pattern of the coal-derived carbon-based nickel diatomic catalyst prepared in the preparation method of the coal-derived carbon-based nickel diatomic catalyst provided in the present application.
[0029] Figure 4 is the nitrogen adsorption-desorption isotherm graph of the coal-derived carbon-based nickel diatomic catalyst prepared in the preparation method of the coal-derived carbon-based nickel diatomic catalyst provided in the present application.
[0030] Figure 5 is the pore size distribution graph of the coal-derived carbon-based nickel diatomic catalyst prepared in the preparation method of the coal-derived carbon-based nickel diatomic catalyst provided in the present application.
[0031] Figure 6 is the nitrogen 1s orbital X-ray photoelectron spectroscopy graph of the coal-derived carbon-based nickel diatomic catalyst prepared in the preparation method of the coal-derived carbon-based nickel diatomic catalyst provided in the present application, the coal-derived carbon-based nickel monatomic catalyst prepared in the preparation of the comparative example 1, and the coal-derived carbon-based nitrogen-doped catalyst prepared in the preparation of the comparative example 2.
[0032] Figure 7 is the nickel 2p orbital X-ray photoelectron spectroscopy graph of the coal-derived carbon-based nickel diatomic catalyst prepared in the preparation method of the coal-derived carbon-based nickel diatomic catalyst provided in the present application. p
[0033] Figure 8 is the nickel 2p near-edge X-ray absorption near-edge structure spectroscopy graph of the coal-derived carbon-based nickel diatomic catalyst prepared in the preparation method of the coal-derived carbon-based nickel diatomic catalyst provided in the present application. k
[0034] Figure 9 is the nickel 2p fine structure spectroscopy graph of the coal-derived carbon-based nickel diatomic catalyst prepared in the preparation method of the coal-derived carbon-based nickel diatomic catalyst provided in the present application. k
[0035] Figure 10 is the nickel 2p fine structure spectroscopy fitting curve of the coal-derived carbon-based nickel diatomic catalyst prepared in the preparation method of the coal-derived carbon-based nickel diatomic catalyst provided in the present application. k
[0036] Figure 11 are linear sweep voltammograms of the coal-derived carbon-based nickel diatomic catalyst prepared in Example 1 of the preparation method of the coal-derived carbon-based nickel diatomic catalyst provided by the present application, the coal-derived carbon-based nickel monatomic catalyst prepared in Comparative Example 1, the coal-derived carbon-based nitrogen-doped catalyst prepared in Comparative Example 2, and the coal-derived carbon-based nickel-doped carbon catalyst prepared in Comparative Example 3.
[0037] Figure 12 are Faraday efficiency fold line graphs of the coal-derived carbon-based nickel diatomic catalysts prepared in Example 1 to Example 3 of the preparation method of the coal-derived carbon-based nickel diatomic catalyst provided by the present application for electrocatalytic reduction of carbon dioxide to carbon monoxide under different applied potentials.
[0038] Figure 13 are Faraday efficiency fold line graphs of the coal-derived carbon-based nickel diatomic catalyst prepared in Example 1 of the preparation method of the coal-derived carbon-based nickel diatomic catalyst provided by the present application, the coal-derived carbon-based nickel monatomic catalyst prepared in Comparative Example 1, the coal-derived carbon-based nitrogen-doped catalyst prepared in Comparative Example 2, and the coal-derived carbon-based nickel-doped carbon catalyst prepared in Comparative Example 3 for electrocatalytic reduction of carbon dioxide to carbon monoxide under different applied potentials.
[0039] Figure 14 are partial current density fold line graphs of the coal-derived carbon-based nickel diatomic catalyst prepared in Example 1 of the preparation method of the coal-derived carbon-based nickel diatomic catalyst provided by the present application, the coal-derived carbon-based nickel monatomic catalyst prepared in Comparative Example 1, the coal-derived carbon-based nitrogen-doped catalyst prepared in Comparative Example 2, and the coal-derived carbon-based nickel-doped carbon catalyst prepared in Comparative Example 3 for electrocatalytic reduction of carbon dioxide to carbon monoxide under different applied potentials.
[0040] Figure 15 is the turnover frequency of the coal-derived carbon-based nickel diatomic catalyst prepared in Example 1 of the preparation method of the coal-derived carbon-based nickel diatomic catalyst provided by the present application for electrocatalytic reduction of carbon dioxide to carbon monoxide under different applied potentials.
[0041] Figure 16 is the turnover frequency of the coal-derived carbon-based nickel monatomic catalyst prepared in Comparative Example 1 for electrocatalytic reduction of carbon dioxide to carbon monoxide under different applied potentials. DETAILED DESCRIPTION
[0042] The embodiments of the present application will be further described in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present application, but cannot be used to limit the scope of the present application.
[0043] As shown in Figures 1 to 16 , the present application provides a coal-derived carbon-based nickel diatomic catalyst, a preparation method thereof, and applications thereof.
[0044] The present invention provides a method for preparing a derived carbon-based nickel diatomic catalyst, which specifically includes the following steps:
[0045] S100. Grind and mix 1g~6g of anthracite and 3g~60g of potassium hydroxide, wherein the ratio of anthracite to potassium hydroxide is 1:3~1:10, to obtain a first mixture; place the first mixture into a tube furnace for activation, wherein the activation temperature is 800℃~1000℃, and after reaching the activation temperature, hold at the temperature for 1 hour~3 hours to obtain an activated product;
[0046] The activated material is washed and dried sequentially to obtain the first material; the washing of the activated material specifically includes the following steps:
[0047] S110, using a concentration of 4 mol / L -1 ~ 8mol L -1 The activated material is first acid-washed with hydrochloric acid to obtain the first wash; this wash is used to remove residual potassium hydroxide from the activated material.
[0048] S120, using a concentration of 5 mol / L -1 ~ 10mol L -1 The first detergent is subjected to a second acid wash with hydrofluoric acid to obtain a second detergent; this is used to remove inorganic matter from the porous carbon of the first detergent.
[0049] S130. The second washing product is washed with water to obtain the first material to be dried; this is used to clean and remove residual hydrochloric acid and hydrofluoric acid in the second washing product; the washing can be done with distilled water or deionized water.
[0050] Further, after drying the first material to be dried, excess moisture is removed to obtain the first material.
[0051] S200, the first material is mixed with a concentration of 4 mol L... -1 ~ 8mol L -1 An oxidizing agent is mixed, wherein the oxidizing agent is one of nitric acid, potassium permanganate or hydrogen peroxide, to obtain a second mixture; the second mixture is heated and oxidized, wherein the heating and oxidation temperature is 80℃~100℃, to obtain an oxide; the oxide is dried to obtain a second material;
[0052] S300, Place the second material into a solution with a concentration of 3 mmol / L. -1 ~ 10mmol L -1 The material is immersed and stirred in a soluble nickel salt solution for 8 to 12 hours, then filtered to obtain the third material; wherein the soluble nickel salt solution is one of nickel chloride solution, nickel nitrate solution or nickel sulfate solution.
[0053] S400: Grind and mix a third material with a nitrogen-containing compound at a mass ratio of 1:5 to 1:15, wherein the nitrogen-containing compound is one of urea, dicyandiamide, or melamine, to obtain a third mixture; add the third mixture to a tube furnace for carbonization at a temperature of 900℃ to 1100℃, and hold at the carbonization temperature for 1 hour to 3 hours to obtain a carbide; sequentially perform acid washing, water washing, and drying on the carbide, wherein a 1 mol L⁻¹ solution is used. -1 ~ 2mol L -1 The carbides were acid-washed with hydrochloric acid solution to remove the nickel clusters formed after carbonization. The acid washing time was 4 to 6 hours to obtain a coal-derived carbon-based nickel diatomic catalyst.
[0054] This invention also provides a coal-derived carbon-based nickel diatomic catalyst, prepared according to the above-described method. The catalyst uses anthracite as raw material and a coal-derived carbon-based material as a precursor. The support is a coal-derived carbon-based porous material mainly composed of micropores and mesopores, constructing an N3Ni-NiN3 diatomic structure. Adjacent NiN3 units are interconnected through Ni atoms to form a specific spatial configuration, aiming to establish a synergistic stabilization mechanism to effectively stabilize the unsaturated Ni-N3 coordination environment, thereby significantly improving the structural stability of the catalyst while maintaining high activity. The coal-derived carbon-based material itself possesses good electrical conductivity, chemical stability, and high specific surface area, providing an ideal support platform for constructing and stabilizing such a fine diatomic structure. The active sites are Ni2-N6, which, compared to Ni-N4 sites, effectively lowers the formation energy barrier for carboxyl intermediates, thereby accelerating the formation rate of carbon monoxide. The nickel atom loading of the catalyst is 0.1%~10%.
[0055] This invention provides a coal-derived carbon-based nickel diatomic catalyst that exhibits a Faradaic efficiency of up to 98.6% for its carbon monoxide product at a potential of -0.8V (relative to the reversible hydrogen electrode). Within a wide potential window range of -0.8 to -1.2V (relative to the reversible hydrogen electrode), the Faradaic efficiency of its carbon monoxide product remains above 94%, and it also possesses a relatively large carbon monoxide bias current density (56.4 mA cm⁻¹ at -1.0V (relative to the reversible hydrogen electrode)). -2 Furthermore, even at an overpotential of 1.19V, it exhibits a high carbon monoxide formation turnover rate of 7885 h. -1 .
[0056] The present invention provides a coal-derived carbon-based nickel diatom catalyst, the preparation process of which is as follows:
[0057] The anthracite coal is rich in source and low in cost, and is activated by potassium hydroxide to form porous carbon;
[0058] The porous carbon is treated by an oxidizing agent to form oxidized carbon, the oxidized carbon adsorbs a soluble nickel salt solution, and then is mixed with a nitrogen-containing compound, carbonized, and pickled to obtain the coal-derived carbon-based nickel diatomic catalyst. 2 The coal-derived carbon-based nickel diatomic catalyst is a porous carbon material, and the specific surface area is greater than 300 m
[0059] The application further provides an application of the coal-derived carbon-based nickel diatomic catalyst in a carbon dioxide electro-reduction reaction.
[0060] Embodiment 1
[0061] The embodiment provides a preparation method of a coal-derived carbon-based nickel diatomic catalyst, and specifically includes the following steps.
[0062] S100, 2g of anthracite coal is mixed with 10g of potassium hydroxide in a marquis mortar, and then is transferred to a corundum boat, and then is placed in a tube furnace, and is heated to 800 DEG C at a rate of 5 DEG C / min under an argon atmosphere, and is kept for 2 hours, and is cooled to room temperature.
[0063] The above material is placed in a beaker containing 100mL of hydrochloric acid solution with a concentration of 8mol / L -1 , and is stirred for 8 hours, and then is washed and filtered with a sand core funnel using deionized water for three times, and is dried in a vacuum drying oven at 80 DEG C overnight, and then is taken out. -1 The dried sample is placed in a polytetrafluoroethylene beaker containing 50mL of hydrofluoric acid solution with a concentration of 10mol / L -1 , and is stirred for 12 hours, and then is naturally settled and filtered in a funnel, and is washed with deionized water for three times, and is dried in a vacuum drying oven at 80 DEG C overnight to obtain activated coal-based activated carbon, which is recorded as a first material.
[0064] S200, the first material is added into a three-necked flask, and then 100mL of nitric acid with a concentration of 4mol / L -1 is added, and is heated at 90 DEG C, and is condensed and refluxed.
[0065] S300, the second material is placed in a beaker containing 40mL of nickel chloride solution with a concentration of 3mmol / L -1 , and is immersed and stirred for 12 hours, and then is filtered, and is dried in a vacuum drying oven at 80 DEG C overnight to obtain a third material.
[0066] S400. The third material and urea are ground and mixed in an agate mortar at a mass ratio of 1:10, then transferred to a corundum boat and placed in a tube furnace. Under an argon atmosphere, the temperature is increased to 1000℃ at a rate of 5℃ / min, held for 1 hour, and then cooled to room temperature. Then, 100 mL of a 2mol / L solution is added. -1 The catalyst was immersed and stirred in a beaker of hydrochloric acid solution for 4 hours, then washed three times with deionized water, and dried overnight in a vacuum drying oven at 80°C to obtain a coal-derived carbon-based nickel diatomic catalyst, named Ni-DACs.
[0067] Example 2
[0068] This embodiment provides a method for preparing a coal-derived carbon-based nickel diatomic catalyst, which specifically includes the following steps:
[0069] S100. Grind and mix 4g of anthracite and 28g of potassium hydroxide in an agate mortar, then transfer the mixture to a corundum boat and place it in a tube furnace. Under an argon atmosphere, heat the mixture to 900℃ at a rate of 5℃ / min, hold it at that temperature for 3 hours, and then cool it to room temperature.
[0070] The above material was placed in 100 mL of a solution with a concentration of 6 mol / L. -1 The sample was stirred in a beaker of hydrochloric acid solution for 8 hours, then filtered three times with deionized water using a sintered glass funnel. After drying in a vacuum oven at 80°C overnight, the dried sample was placed in 50 mL of 8 mol / L hydrochloric acid solution. -1 The polytetrafluoroethylene solution was stirred in a beaker containing hydrofluoric acid for 12 hours, then allowed to settle naturally in a funnel for filtration, washed three times with distilled water, and dried overnight in a vacuum drying oven at 80°C to obtain activated coal-based activated carbon, which was designated as the first material.
[0071] S200. Add the first material to a three-necked flask, then add 100 mL of a 6 mol / L solution. -1 Potassium permanganate was heated at 90°C and refluxed. It was then washed three times with distilled water and dried overnight in a vacuum drying oven at 80°C to obtain the second material.
[0072] S300, Place the second material into a container containing 40 mL of a solution with a concentration of 7 mmol / L. -1 The solution of nickel nitrate was immersed and stirred in a beaker for 10 hours, then filtered, and dried overnight in a vacuum drying oven at 80°C to obtain the third material.
[0073] S400: The third material and dicyandiamide were ground and mixed in an agate mortar at a mass ratio of 1:15, then transferred to a corundum boat and placed in a tube furnace. Under an argon atmosphere, the mixture was heated to 900°C at a rate of 5°C / min, held at that temperature for 1 hour, and then cooled to room temperature. Subsequently, 100 mL of a 1.5 mol / L solution was added. -1 The catalyst was immersed and stirred in a beaker of hydrochloric acid solution for 5 hours, then washed three times with deionized water, and dried overnight in a vacuum drying oven at 80°C to obtain a coal-derived carbon-based nickel diatomic catalyst, named Ni-DACs-900.
[0074] Example 3
[0075] This embodiment provides a method for preparing a coal-derived carbon-based nickel diatomic catalyst, which specifically includes the following steps:
[0076] S100. Grind and mix 6g of anthracite and 60g of potassium hydroxide in an agate mortar, then transfer the mixture to a corundum boat and place it in a tube furnace. Under an argon atmosphere, heat the mixture to 1000℃ at a rate of 5℃ / min, hold it at that temperature for 2 hours, and then cool it to room temperature.
[0077] The above material was placed in 100 mL of a solution with a concentration of 4 mol / L. -1 The sample was stirred in a beaker of hydrochloric acid solution for 8 hours, then filtered three times with deionized water using a sintered glass funnel. After drying in a vacuum oven at 80°C overnight, the dried sample was placed in 50 mL of a 5 mol / L solution. -1 The polytetrafluoroethylene solution was stirred in a beaker containing hydrofluoric acid for 12 hours, then allowed to settle naturally in a funnel for filtration, washed three times with deionized water, and dried overnight in a vacuum drying oven at 80°C to obtain activated coal-based activated carbon, which was designated as the first material.
[0078] S200. Add the first material to a three-necked flask, then add 100 mL of 8 mol / L solution. -1 Hydrogen peroxide was heated at 90°C and refluxed. It was then washed three times with deionized water and dried overnight in a vacuum drying oven at 80°C to obtain the second material.
[0079] S300, Place the second material into 40 mL of a solution with a concentration of 10 mmol / L. -1 The solution of nickel sulfate was immersed and stirred in a beaker for 12 hours, then filtered, and dried overnight in a vacuum drying oven at 80°C to obtain the third material.
[0080] S400: The third material and melamine are ground and mixed in an agate mortar at a mass ratio of 1:5, then transferred to a corundum boat and placed in a tube furnace. Under an argon atmosphere, the temperature is increased to 1100℃ at a rate of 5℃ / min, held for 1 hour, and then cooled to room temperature. Then, 100 mL of a 1 mol / L solution is added. -1 The catalyst was immersed and stirred in a beaker of hydrochloric acid solution for 4 hours, then washed three times with deionized water, and dried overnight in a vacuum drying oven at 80°C to obtain a coal-derived carbon-based nickel diatomic catalyst, named Ni-DACs-1100.
[0081] Comparative Example 1
[0082] This comparative example provides a method for preparing a coal-derived carbon-based nickel single-atom catalyst, specifically including the following steps:
[0083] S100. Grind and mix 2g of anthracite and 10g of potassium hydroxide in an agate mortar, then transfer the mixture to a corundum boat and place it in a tube furnace. Under an argon atmosphere, heat the mixture to 800℃ at a rate of 5℃ / min, hold it at that temperature for 2 hours, and then cool it to room temperature.
[0084] The above material was placed in 100 mL of a solution with a concentration of 8 mol / L. -1 The sample was stirred in a beaker of hydrochloric acid solution for 8 hours, then washed and filtered three times with deionized water using a sintered glass funnel. After drying in a vacuum oven at 80°C overnight, the dried sample was placed in 50 mL of a 10 mol / L solution. -1 The polytetrafluoroethylene solution was stirred in a beaker containing hydrofluoric acid for 12 hours, then allowed to settle naturally in a funnel for filtration, washed three times with deionized water, and dried overnight in a vacuum drying oven at 80°C to obtain activated coal-based activated carbon, which was designated as the first material.
[0085] S200, Place the first material into a container of 40 mL of 3 mmol / L solution. -1 The solution of nickel chloride was immersed and stirred in a beaker for 12 hours, then washed three times with deionized water, and dried overnight in a vacuum drying oven at 80°C to obtain the third material.
[0086] S300: The third material and urea are ground and mixed in an agate mortar at a mass ratio of 1:10, then transferred to a corundum boat and placed in a tube furnace. Under an argon atmosphere, the temperature is increased to 1000℃ at a rate of 5℃ / min, held for 1 hour, and then cooled to room temperature. Then, 100 mL of a 2mol / L solution is added. -1 The catalyst was immersed and stirred in a beaker of hydrochloric acid solution for 4 hours, then washed three times with deionized water, and dried overnight in a vacuum drying oven at 80°C to obtain a coal-derived carbon-based nickel single-atom catalyst, named Ni-SACs.
[0087] Comparative Example 2
[0088] The present comparative example provides a preparation method of a coal-derived carbon-based nitrogen-doped carbon catalyst, specifically comprising the following steps:
[0089] S100, 2g anthracite coal and 10g potassium hydroxide were mixed by grinding in an agate mortar, then transferred to a corundum boat, and then placed in a tube furnace, heated to 800°C at a rate of 5°C / min under an argon atmosphere, kept for 2 hours, and cooled to room temperature.
[0090] The above material was placed in a beaker containing 100mL of 8mol / L -1 hydrochloric acid solution and stirred for 8h, then filtered three times using a sand core funnel and washed with deionized water, and then taken out after drying overnight in a vacuum drying oven at 80°C. Then the dried sample was placed in a polytetrafluoroethylene beaker containing 50mL of 10mol / L -1 hydrofluoric acid solution and stirred for 12 hours, then naturally settled and filtered in a funnel, washed three times with deionized water, and dried overnight in a vacuum drying oven at 80°C to obtain activated coal-based activated carbon, denoted as the first material.
[0091] S200, the first material was added to a three-necked flask, then 100mL of 4mol / L -1 nitric acid was added, heated at 90°C, and condensed refluxed. Then washed three times with deionized water and dried overnight in a vacuum drying oven at 80°C to obtain the second material.
[0092] S300, the second material was mixed with urea in a mass ratio of 1:10 by grinding in an agate mortar, then transferred to a corundum boat, and then placed in a tube furnace, heated to 1000°C at a rate of 5°C / min under an argon atmosphere, kept for 1 hour, and cooled to room temperature. Then immersed and stirred in a beaker containing 100mL of 2mol / L -1 hydrochloric acid solution for 4 hours, then washed three times with deionized water and dried overnight in a vacuum drying oven at 80°C to obtain a coal-derived carbon-based nitrogen-doped carbon catalyst, denoted as N-C.
[0093] Comparative Example 3
[0094] The present comparative example provides a preparation method of a coal-derived carbon-based nickel-doped carbon catalyst, specifically comprising the following steps:
[0095] S100, 2g anthracite coal and 10g potassium hydroxide were mixed by grinding in an agate mortar, then transferred to a corundum boat, and then placed in a tube furnace, heated to 800°C at a rate of 5°C / min under an argon atmosphere, kept for 2 hours, and cooled to room temperature.
[0096] The above material was placed in a beaker containing 100 mL of a 8 mol L -1 hydrochloric acid solution and stirred for 8 h, then filtered using a sand core funnel and washed with deionized water three times, and dried in a vacuum drying oven at 80℃ overnight. The dried sample was then placed in a polytetrafluoroethylene beaker containing 50 mL of a 10 mol L -1 hydrofluoric acid solution and stirred for 12 h, then naturally settled and filtered in a funnel, washed with deionized water three times, and dried in a vacuum drying oven at 80℃ overnight to obtain an activated coal-based activated carbon, denoted as a first material.
[0097] S200, the first material was added to a three-necked flask, then 100 mL of a 4 mol L -1 nitric acid was added, and heated at 90℃ with condensation reflux. Subsequently, the second material was obtained by washing with deionized water three times and drying in a vacuum drying oven at 80℃ overnight.
[0098] S300, the second material was placed in a beaker containing 40 mL of a 3 mmol L -1 nickel chloride solution and immersed and stirred for 12 h, then filtered, and dried in a vacuum drying oven at 80℃ overnight to obtain a third material.
[0099] S400, the third material was transferred to a corundum boat, then placed in a tube furnace, and heated to 1000℃ at a rate of 5℃ / min under an argon atmosphere, and held for 1 h, and then cooled to room temperature. Subsequently, the material was immersed and stirred in a beaker containing 100 mL of a 2 mol L -1 hydrochloric acid solution for 4 h, then washed with deionized water three times, and dried in a vacuum drying oven at 80℃ overnight to obtain a coal-derived carbon-based nickel-doped carbon catalyst, denoted as Ni-C.
[0100] The material usage and product structure parameter comparison of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3 are shown in Table 1.
[0101] Table 1 Material usage and product structure parameters
[0102]
[0103] The performance comparison results of the products of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3 with the Ni-N3 single-atom catalyst in the prior art are shown in Table 2.
[0104] Table 2 Performance comparison
[0105]
[0106] The comparison results of the nickel element content in the products of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 3 are shown in Table 3.
[0107] Table 3 Nickel element content
[0108]
[0109] Figure 1 The scanning electron microscope image of the coal-derived carbon-based nickel bimetallic catalyst prepared in Example 1 of the present application. It can be seen from the image that the catalyst is a porous carbon material, and the whole presents a porous shape.
[0110] Figure 2 The transmission electron microscope image of the coal-derived carbon-based nickel bimetallic catalyst prepared in Example 1 of the present application; Figure 3 The electron diffraction image of the coal-derived carbon-based nickel bimetallic catalyst prepared in Example 1 of the present application. From the image, it can be seen that the catalyst is amorphous carbon. Figure 2 And Figure 3 It can be seen that the catalyst is amorphous carbon.
[0111] Figure 4 The nitrogen adsorption-desorption isotherm graph of the coal-derived carbon-based nickel bimetallic catalyst prepared in Example 1 to Example 3 of the present application. It can be seen from the graph that the catalyst contains a large amount of micropores and a certain amount of mesopores, and the specific surface area gradually decreases with the increase of the treatment temperature.
[0112] Figure 5 The pore size distribution graph of the coal-derived carbon-based nickel bimetallic catalyst prepared in Example 1 to Example 3 of the present application. It can be seen from the graph that the catalyst is mainly microporous and mesoporous, and the pore volume of the microporous and mesoporous gradually decreases with the increase of the treatment temperature.
[0113] Figure 6 The nitrogen 1s orbit X-ray photoelectron spectroscopy graph of the coal-derived carbon-based nickel bimetallic catalyst, the coal-derived carbon-based nickel monometallic catalyst and the coal-derived carbon-based nitrogen-doped carbon catalyst prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present application. It can be seen from the graph that the nitrogen 1s orbit spectrum of the products of Example 1 and Comparative Example 1 can be divided into the following five kinds: pyridine nitrogen (about 398.3 eV), metal nitrogen (about 399.3 eV), pyrrole nitrogen (about 400.3 eV), graphite nitrogen (about 401.2 eV) and oxidized nitrogen (about 403.4 eV); the product of Example 2 does not contain metal nitrogen.
[0114] Figure 7 The nickel 2p orbit X-ray photoelectron spectroscopy graph of the coal-derived carbon-based nickel bimetallic catalyst prepared in Example 1 of the present application. It can be seen from the graph that the nickel 2p orbit spectrum of the product of Example 1 can be divided into the following two kinds: metallic nickel (about 852.8 eV) and oxidized nickel (about 855.6 eV). p The nickel 2p orbit X-ray photoelectron spectroscopy graph of the coal-derived carbon-based nickel bimetallic catalyst prepared in Example 1 of the present application. It can be seen from the graph that the nickel 2p orbit spectrum of the product of Example 1 can be divided into the following two kinds: metallic nickel (about 852.8 eV) and oxidized nickel (about 855.6 eV). pThe orbital X-ray photoelectron spectroscopy (ORS) falls between the metallic state of nickel (852.5 - 853.0 eV) and the divalent state of nickel (855.7 - 856.0 eV), indicating that the valence state of the nickel species is between 0 and 2. + between.
[0115] Figure 8 The nickel in the coal-derived carbon-based nickel diatomic catalyst prepared in Example 1 of this invention. k Near-edge X-ray absorption spectrum. As can be seen from the figure, the absorption edge of the product in Example 1 is located between the nickel foil and the nickel phthalocyanine (NiPc) reference values, indicating that the valence state of nickel is between 0 and 2. + between.
[0116] Figure 9 The nickel in the coal-derived carbon-based nickel diatomic catalyst prepared in Example 1 of this invention. k Fine structure X-ray absorption spectra. As can be seen from the figure, the main peak in the product of Example 1 is at 1.41 Å, corresponding to the nickel-nitrogen scattering path. Meanwhile, the nickel-nickel scattering path, representing the nickel-nickel coordination relationship, appears at approximately 2.02 Å, indicating that both nickel-nitrogen coordination and directly connected nickel-nickel coordination are present in the product.
[0117] Figure 10 The nickel in the coal-derived carbon-based nickel diatomic catalyst prepared in Example 1 of this invention. k Fitting curves of edge X-ray absorption fine structure spectrum (R space). As can be seen from the figure, the experimental results show that the fitting effect is good.
[0118] Figure 11 This is Example 1 of the present invention, showing the linear sweep voltammetry curves of the coal-derived carbon-based nickel diatom catalyst, coal-derived carbon-based nickel singleatom catalyst, coal-derived carbon-based nitrogen-doped carbon catalyst, and coal-derived carbon-based nickel-doped carbon catalyst prepared in Comparative Examples 1, 2, and 3. As can be seen from the figures, the current density of the product in Example 1 is significantly higher than that of the products in Comparative Examples 1, 2, and 3.
[0119] Figure 12 The graphs show the Faradaic efficiency of the electrocatalytic reduction of carbon dioxide to carbon monoxide for the products of Examples 1 to 3 of this invention at different applied potentials. As can be seen from the graphs, the carbon monoxide Faradaic efficiency of the products of Examples 1 and 2 both exceeded 90% at potentials ranging from -0.8V to -1.2V (relative to the reversible hydrogen electrode). Specifically, the carbon monoxide Faradaic efficiency of the product of Example 1 was higher than that of the product of Example 2.
[0120] Figure 13This invention is illustrated in Example 1, Comparative Examples 1, 2, and 3, showing the Faradaic efficiency of the coal-derived carbon-based nickel diatom catalyst, coal-derived carbon-based nickel singleatom catalyst, coal-derived carbon-based nitrogen-doped carbon catalyst, and coal-derived carbon-based nickel-doped carbon catalyst for the electrocatalytic reduction of carbon dioxide to carbon monoxide at different applied potentials. The graphs show that the product of Example 1 achieved the highest carbon monoxide Faradaic efficiency of 98.6% at -0.8V (relative to the reversible hydrogen electrode), and its carbon monoxide Faradaic efficiency exceeded 94% over a relatively wide negative potential range of -0.8 to -1.2V (relative to the reversible hydrogen electrode).
[0121] Figure 14 This is Example 1 of the present invention, showing the bias current density of the coal-derived carbon-based nickel diatom catalyst, coal-derived carbon-based nickel singleatom catalyst, coal-derived carbon-based nitrogen-doped carbon catalyst, and coal-derived carbon-based nickel-doped carbon catalyst prepared in Comparative Examples 1, 2, and 3, at different applied potentials. As can be seen from the figures, compared with the products of Comparative Examples 1, 2, and 3, the product of Example 1 exhibits the highest bias current density for carbon monoxide. Furthermore, at a potential of -1.0V (relative to the reversible hydrogen electrode), the bias current density of carbon monoxide in the product of Example 1 reaches as high as 56.4 mA cm⁻¹. -2 ;
[0122] Figure 15 and Figure 16 The figure shows the turnover frequency of the coal-derived carbon-based nickel diatomic catalyst and the coal-derived carbon-based nickel single-atom catalyst prepared in Example 1 and Comparative Example 1 of this invention, respectively, for the electrocatalytic reduction of carbon dioxide to carbon monoxide at different applied potentials. As can be seen from the figure, the turnover frequency value for quality correction in the product of Example 1 is 2165 h. -1 Comparison Example 1 product at -0.8V (relative to the reversible hydrogen electrode) for 206 hours -1 This is approximately 10.5 times higher. Simultaneously, at an overpotential of 1.19V (-1.3V (relative to the reversible hydrogen electrode)), the turnover frequency for quality correction in the product of Example 1 reached 7885 hours. -1 The comparative example product was 1129h. -1 Furthermore, the product of Example 1 has a turnover rate of 5361 h for electrochemically active surface area correction at -0.8V (relative to the reversible hydrogen electrode). -1 This value is approximately equal to that of Comparative Example 1 product (477h) -1 The electrochemically active surface area correction turnover rate of the product in Example 1 reached 19522 h at -1.3 V (relative to the reversible hydrogen electrode). -1 It is far higher than that of Comparative Example 1 product (2615h) -1 ).
[0123] The application provides a coal-derived carbon-based nickel double-atom catalyst, a preparation method and application thereof, and the coal-derived carbon-based nickel double-atom catalyst is prepared by using anthracite as a carbon source, a nitrogen-containing compound as a nitrogen source, and a soluble nickel salt solution as a nickel source through an activation, oxidation and high-temperature carbonization method, high-value utilization of the anthracite is realized, the cost is low, the process is simple, and the yield is high; the coal-derived carbon-based nickel double-atom catalyst prepared has good catalytic performance, the active site of the catalyst is Ni2-N6, the structure is stable, the generation energy barrier of a carboxyl radical intermediate can be effectively reduced, and the generation rate of carbon monoxide is accelerated.
[0124] Finally, it should be noted that: the above examples are only used to illustrate the technical solutions of the present application, and not to limit them; although the present application has been described in detail with reference to the foregoing examples, those skilled in the art should understand that: it can still modify the technical solutions recorded in the foregoing examples, or make equivalent replacement for part of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A method of preparing a coal-derived carbon-based nickel biatomic catalyst, characterized by, The method comprises the following steps: S100, grinding and mixing anthracite and potassium hydroxide to obtain a first mixture; placing the first mixture into a tube furnace for activation to obtain an activated product; sequentially washing, drying the activated product to obtain a first material; The washing of the activated product comprises the following steps: S110, using a concentration of 4 mol / L -1 ~ 8 mol L -1 The activated material was first acid-washed with hydrochloric acid to obtain a first wash product; S120, using a concentration of 5 mol / L -1 ~ 10 mol L -1 The first detergent is subjected to a second acid wash with hydrofluoric acid to obtain a second detergent. S130, washing the second washing product with water to obtain the first material to be dried; S200, mixing the first material with an oxidizing agent to obtain a second mixture; heating and oxidizing the second mixture to obtain an oxidized product; drying the oxidized product to obtain a second material; wherein the oxidizing agent is one of nitric acid, potassium permanganate or hydrogen peroxide; S300: The second material is immersed and stirred in a soluble nickel salt solution, then filtered to obtain the third material; the concentration of the soluble nickel salt solution is 3 ~ 10 mmol / L. -1 The stirring time is 8 to 12 hours; the soluble nickel salt solution is one of nickel chloride solution, nickel nitrate solution or nickel sulfate solution; S400, grinding and mixing the third material with a nitrogen-containing compound to obtain a third mixture; placing the third mixture into a tube furnace for carbonization to obtain a carbonized product; sequentially acid washing, washing with water, drying the carbonized product to obtain a coal-derived carbon-based nickel double-atom catalyst; the carbonization temperature is 900-1100 DEG C, and after reaching the carbonization temperature, the temperature is maintained for 1-3 hours; The active site of the coal-derived carbon-based nickel double-atom catalyst is Ni2-N6, and the nickel atom loading of the coal-derived carbon-based nickel double-atom catalyst is 0.1-10 %. The coal-derived carbon-based nickel double-atom catalyst is applied to a carbon dioxide electro-reduction reaction.
2. The method of claim 1, wherein the coal-derived carbon-based nickel biatomic catalyst is prepared by the steps of: In the S100 step, the weight of the anthracite is 1-6 g, and the weight of the potassium hydroxide is 3-60 g.
3. The method for preparing the coal-derived carbon-based nickel diatomic catalyst according to claim 1, characterized in that, In the S100 step, the activation temperature is 800-1000 DEG C, and after reaching the activation temperature, the temperature is maintained for 1-3 hours.
4. The method of claim 1, wherein the coal-derived carbon-based nickel biatomic catalyst is prepared by the steps of: The concentration of the oxidizing agent in the S200 step is 4 mol / L -1 8 mol / L -1 The temperature of the heating oxidation is 80℃~100℃.
5. The method of claim 1, wherein the coal-derived carbon-based nickel biatomic catalyst is prepared by the steps of: In the S400 step, the acid washing of the carbonized product comprises the following steps: The carbide is pickled with a hydrochloric acid solution having a concentration of 1 mol L -1 2 mol L -1 for 4 to 6 hours.
6. A coal-derived carbon-based nickel double-atom catalyst prepared by the preparation method of any one of claims 1-5.
7. The application of the coal-derived carbon-based nickel double-atom catalyst of claim 6 in a carbon dioxide electro-reduction reaction.
Citation Information
Patent Citations
Preparation method of nitrogen-doped porous carbon and catalytic application thereof in fuel cell cathode
CN109678153A